(untitled) (Research, Society and Development, 2022)
This study aimed at evaluating retrospective data in order to establish non-genetic and genetic parameters of In Vitro Embryo Production (IVP) of the Nelore breed, in the State of Acre, Brazil. Therefore, data from 1,292 sessions of ultrasound-guided follicular aspirations performed in 571 Nellore donors, distributed in ten farms in Acre, between 2015 and 2018, were collected and analyzed in order to estimate production and non-genetic parameters, by using the Generalized Least Squares Method with SAS Software, and genetic effects by the Restricted Maximum Likelihood Method, by using MTDFREML software. Mean values ​​for number of oocytes, embryos and pregnancy by aspiration per cow of 30.05, 9.82 and 3.03, were respectively obtained; and mean conversion rates of oocyte/embryo, embryo/pregnancy and oocyte/pregnancy of 34.19; 38.39 and 10.68%, respectively. For the genetic effects, it was observed that the heritability presented low to medium magnitude, thus indicating genetic variability for the production of oocytes, embryos and pregnancy. Phenotypic and genetic correlations between total number of oocytes, embryos and pregnancy were positive and of high magnitude, indicating that selection for increased oocyte production results in increased embryo production and pregnancy rate. It is concluded that the non-genetic effects on In Vitro Embryo Production should be considered in the genetic evaluation models for these traits, and the heritability estimates found in this study, despite being of low to moderate magnitudes, indicate that there is additive genetic variability for the selection of donors with the best genetic potential for the production of oocytes, embryos and pregnancies.